NOTCH target gene HES5 mediates oncogenic and tumor suppressive functions in hepatocarcinogenesis - Luiken, Sarah; Fraas, Angelika; Bieg, Matthias; Sugiyanto, Raisatun Nisa; Goeppert, Benjamin; Singer, Stephan; Plöger, Carolin; Warsow, Gregor; Marquardt, Jens; Sticht, Carsten; Torre, Carolina de la; Pusch, Stefan; et al. (Oncogene, 2020)
NOTCH receptor signaling plays a pivotal role in liver homeostasis and hepatocarcinogenesis. However, the role of NOTCH pathway mutations and the NOTCH target gene HES5 in liver tumorigenesis are poorly understood. Here we performed whole-exome sequencing of 54 human HCC specimens and compared the prevalence of NOTCH pathway component mutations with the TCGA-LIHC cohort (N = 364). In addition, we functionally characterized the NOTCH target HES5 and the patient-derived HES5-R31G mutation in vitro and in an orthotopic mouse model applying different oncogenic backgrounds, to dissect the role of HES5 in different tumor subgroups in vivo. We identified nonsynonymous mutations in 14 immediate NOTCH pathway genes affecting 24.1% and 16.8% of HCC patients in the two independent cohorts, respectively. Among these, the HES5-R31G mutation was predicted in silico to have high biological relevance. Functional analyses in cell culture showed that HES5 reduced cell migration and clonogenicity. Further analyses revealed that the patient-derived HES5-R31G mutant protein was non-functional due to loss of DNA binding and greatly reduced nuclear localization. Furthermore, HES5 exhibited a negative feedback loop by directly inhibiting the NOTCH target HES1 and downregulated the pro-proliferative MYC targets ODC1 and LDHA. Interestingly, HES5 inhibited MYC-dependent hepatocarcinogenesis, whereas it promoted AKT-dependent liver tumor formation and stem cell features in a murine model. Thus, NOTCH pathway component mutations are commonly observed in HCC. Furthermore, the NOTCH target gene HES5 has both pro- and anti-tumorigenic functions in liver cancer proposing a driver gene dependency and it promotes tumorigenesis with its interaction partner AKT.
Gesehen am 02.09.2021